2020
DOI: 10.1177/1043659620950447
|View full text |Cite
|
Sign up to set email alerts
|

Instructive Messages and Lessons From Chinese Countermarching Nurses of Caring for COVID-19 Patients: A Qualitative Study

Abstract: Introduction: The World Health Organization declared the COVID-19 outbreak as a Public Health Emergency of International Concern on January 31, 2020. China was the first country to experience the challenges of controlling COVID-19. Therefore, the purpose of this study was to examine the experiences of Chinese nurses who countermarched to the outbreak city for medical support in the very first period of this global infection. Methodology: A qualitative study of phenomenological research design was used to descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
77
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(85 citation statements)
references
References 28 publications
(32 reference statements)
4
77
0
3
Order By: Relevance
“…Data collection methods included semistructured, one‐on‐one, and in‐depth interviews. Several studies used video calls, smartphone applications, or telephone calls for their interviews (He et al 2020; Kackin et al 2020; Zhang et al 2020). Four different analytical methods were utilized: thematic analysis ( n = 1), category analysis ( n = 1), content analysis ( n = 2), and Colaizzi analysis ( n = 5).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Data collection methods included semistructured, one‐on‐one, and in‐depth interviews. Several studies used video calls, smartphone applications, or telephone calls for their interviews (He et al 2020; Kackin et al 2020; Zhang et al 2020). Four different analytical methods were utilized: thematic analysis ( n = 1), category analysis ( n = 1), content analysis ( n = 2), and Colaizzi analysis ( n = 5).…”
Section: Resultsmentioning
confidence: 99%
“…First, nurses in every study reported shortages in personal protective equipment (PPE), equipment such as protective masks and hand sanitizer that is essential to protecting healthcare workers who deliver direct care to patients with COVID‐19 (Kacken et al 2020). In He et al (2020), nurses worked without PPE altogether or with inadequate PPE. Nurses in Schroeder et al (2020) reported that they reused their masks and gowns because they did not have enough supplies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations